2007
DOI: 10.1161/01.res.0000260179.43672.fe
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of Erythropoietin Receptor to Promote VEGF Expression and Angiogenesis in Peripheral Ischemia in Mice

Abstract: Abstract-We have recently demonstrated that endogenous erythropoietin (Epo)/Epo receptor (EpoR) system plays an important protective role in hypoxia-induced pulmonary hypertension. However, it remains to be examined whether vascular EpoR system contributes to angiogenesis in response to ischemia. We examined angiogenesis in EpoR Ϫ/Ϫ -rescued mice that lack EpoR in most organs including cardiovascular system except erythroid-lineage cells. Two weeks after femoral artery ligation, blood flow recovery, activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(110 citation statements)
references
References 39 publications
5
102
1
2
Order By: Relevance
“…Evidence from the study hypothesized that increase in the expression and activation of EPOR can be triggered by VEGF-A, present in the vascular endothelium, upon binding to VEGF receptor-2 (VEGFR-2). 34,36,51 Phosphorylated VEGFR-2 then interacts with phosphorylated EPOR to enhance angiogenesis via a STAT3 signaling pathway 51 and this was equally reported by Nakano et al, 52 Sautina et al, 53 and Yang et al 54 In conclusion, the EPO also modulates angiogenesis by inducing the secretion of VEGF, which then binds and activates VEGFR-2. [51][52][53][54] Apart from VEGFR-2, Sautina et al 53 also demonstrated that the stimulation of EPO is dependent on the βcR.…”
Section: The Role Of Epo In the Eyementioning
confidence: 89%
See 1 more Smart Citation
“…Evidence from the study hypothesized that increase in the expression and activation of EPOR can be triggered by VEGF-A, present in the vascular endothelium, upon binding to VEGF receptor-2 (VEGFR-2). 34,36,51 Phosphorylated VEGFR-2 then interacts with phosphorylated EPOR to enhance angiogenesis via a STAT3 signaling pathway 51 and this was equally reported by Nakano et al, 52 Sautina et al, 53 and Yang et al 54 In conclusion, the EPO also modulates angiogenesis by inducing the secretion of VEGF, which then binds and activates VEGFR-2. [51][52][53][54] Apart from VEGFR-2, Sautina et al 53 also demonstrated that the stimulation of EPO is dependent on the βcR.…”
Section: The Role Of Epo In the Eyementioning
confidence: 89%
“…39,53 This study proposed that NO stimulation was regulated by the heterotrimeric interaction between EPOR/βcR/VEGF-R2 upon binding of EPO to EPOR/βcR. 39,[51][52][53][54][55] Meanwhile, studies have reported that genetic polymorphism in the EPO gene may be a pathogenic factor for acquiring risk of proliferative DR. 56 Katsura et al 55 showed that vitreous EPO was present in significantly higher amount in proliferative DR patients than in macular hole patients who had no retinopathy. The authors further showed the high EPO concentration was not induced by systemic anemia.…”
Section: The Role Of Epo In the Eyementioning
confidence: 99%
“…We also used rabbit anti-human integrin β -1 (M-106) and goat anti-human integrin β -3 (N-20) polyclonal antibody (Sigma, St. Louis, MO, USA) as primary antibodies. We also used alkaline phosphatase-conjugated goat anti-mouse secondary antibody (American Qualex, San Clemente, CA, USA), alkaline phosphatase-conjugated swine anti-rabbit secondary antibody (Dako, Glostrup, Denmark), and alkaline phosphatase-conjugated rabbit anti-goat secondary antibody (Sigma, St. Louis, MO, USA) (Nakano et al 2007;Saji et al 2007;Do e et al 2009). …”
Section: Reagentsmentioning
confidence: 99%
“…The membrane was developed with 5-bromo-4-chloro-3-indolyl phosphate and nitro blue tetrazolium. Signals were visualized by the ECL detection system (Amersham Biosciences, Uppsala, Sweden) (Nakano et al 2007;Do e et al 2009). …”
Section: Western Blot Analysismentioning
confidence: 99%
“…It was found that it also has antiapoptotic, antioxidative and angiogenetic effects that can be used to avoid and treat tissue damage in general. 5,6 This is possible, because of the widespread distribution of the EPO receptor that can mediate non-hematopoietic effects.…”
mentioning
confidence: 99%